10.1016/s1541-9800(05)70518-4 (CrossRef Listing of Deleted DOIs, 2000)
Congenital abnormalities of the kidney and urinary tract (CAKUT) encompass diverse diagnoses that commonly present as urinary tract dilatation and are the leading cause of kidney failure in children. Antenatal hydronephrosis occurs in ~1% of pregnancies; most resolve spontaneously, but conditions such as posterior urethral valves (PUV), pelviureteric junction obstruction (PUJO), vesicoureteric junction obstruction (VUJO), duplex systems, ureteroceles, and vesicoureteric reflux (VUR) require specific approaches to diagnosis and management. Postnatal surveillance relies predominantly on renal tract ultrasound, with micturating cystourethrogram and nuclear scintigraphy used in specific scenarios to define diagnoses, confirm obstruction, and quantify differential function. Urinary tract infections (UTIs) are common and can cause significant morbidity, including sepsis and long-term scarring; prevention of febrile UTIs (fUTIs) is often a central goal. PUV is often associated with a high risk of kidney impairment and fUTI, with early diagnosis, bladder drainage, valve incision, circumcision, and antibiotic prophylaxis shown to reduce UTI risk. VUJO and duplex anomalies carry variable fUTI risk influenced by ureteric dilation and ureteroceles; endoscopic and surgical interventions are effective when indicated. Primary VUR management emphasises bladder-bowel dysfunction treatment, selective antibiotic prophylaxis, and endoscopic injection for recalcitrant fUTIs. Routine prophylaxis is not recommended for isolated unilateral hydronephrosis without distal ureteric dilatation. Management balances infection prevention, renal preservation, and functional outcomes.